Mobility on the Climate Test Bench: Rail Transport - Alexander Eisenkopf (Wirtschaftsdienst)
Abstract Since the transport sector has been violating climate policy targets for some time, suitable transport policy measures are necessary to change this. A greater use of the railways always plays a prominent role in policy strategies. However, achieving the goals for modal shift formulated in the coalition agreement of the new German government by 2030 is questionable. Despite the foreseeable limitations of a modal shift policy, a market-oriented increase in the efficiency and service quality of rail transport is impossible. The focus of climate policy efforts, therefore, should be on road transport where the establishment of emissions trading could overcome small-scale and counterproductive regulations.